A Single‐Step Synthesis of Electroactive Mesoporous ProDOT‐Silica Structures1. Issue 29 (3rd June 2015) - Kim, Jeonghun; Kim, Byeonggwan; Anand, Chokkalingam; Mano, Ajayan; Zaidi, Javaid S. M.; Ariga, Katsuhiko; You, Jungmok; Vinu, Ajayan; Kim, Eunkyoung
Abstract The single‐step preparation of highly ordered mesoporous silica hybrid nanocomposites with conjugated polymers was explored using a novel cationic 3, 4‐propylenedioxythiophene (ProDOT) surfactant (PrS). The method does not require high‐temperature calcination or a washing procedure. The combination of self‐assembly of the silica surfactant and in situ polymerization of the ProDOT tail is responsible for creation of the mesoporosity with ultralarge pores, large pore volume, and electroactivity. As this novel material exhibits excellent textural parameters together with electrical conductivity, we believe that this could find potential applications in various fields. This novel concept of creating mesoporosity without a calcination process is a significant breakthrough in the field of mesoporous materials and the method can be further generalized as a rational preparation of various mesoporous hybrid materials having different structures and pore diameters.